n-4 = n-1-3 chia hết cho n-1
=> 3 chia hết cho n-1
=> n-1 thuộc ước của 3
=> n- 1 thuộc ( \(\pm1;\pm3\))
Với n-1=1 => n =2
Với n-1=-1 => n=0
Với n-1=3 => n=4
Với n-1=-3 => n=-2
Vậy n thuộc (2;0;4;-2)
n-4 = n-1-3 chia hết cho n-1
=> 3 chia hết cho n-1
=> n-1 thuộc ước của 3
=> n- 1 thuộc ( )
Với n-1=1 => n =2
Với n-1=-1 => n=0
Với n-1=3 => n=4
Với n-1=-3 => n=-2
Vậy n thuộc (2;0;4;-2)
-4 = n-1-3 chia hết cho n-1
=> 3 chia hết cho n-1
=> n-1 thuộc ước của 3
=> n- 1 thuộc ( )
Với n-1=1 => n =2
Với n-1=-1 => n=0
Với n-1=3 => n=4
Với n-1=-3 => n=-2
Vậy n thuộc (2;0;4;-2)